(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Progressing processes of globalisation cause increased expectations of external andinternal receivers of financial data. They make necessary for the accounting that the datarelated to financial statement be universally presentable. Standardisation has become acommon process, which is expressed in the normalisation of methods of identification,measurement and definition of components forming the statement. One of the organisations that have had significant impact on the quality of thePolish accounting is the Polish National Accounting Standards Committee. Thisorganisation has published three standards of accounting. It also gives opinions on legalaccounting acts, analyses the International Accounting Standards, accounting standardsdevised by other countries and the European Union directives. The organisationcooperates with international organisations dealing with standardisation of accountingand undertakes other activities aiming at harmonisation and standardisation of rules ofaccounting.